The Auriga stellar haloes: connecting stellar population properties with accretion and merging history - Monachesi, Antonela; Grand, Robert J. J.; Pakmor, Rüdiger; Springel, Volker (Monthly notices of the Royal Astronomical Society, 2019)
Abstract. We examine the stellar haloes of the Auriga simulations, a suite of 30 cosmological magnetohydrodynamical high-resolution simulations of Milky Way-ma
Gesehen am 27.05.2019